EKSPLORASI HABITAT BAKUNG PUTIH (Crinum Asiaticum L.) UNTUK MENDAPATKAN KADAR GALANTAMIN PADA KETINGGIAN TEMPAT BERBEDA - Dewi Estu; Rina Ratnasih Irwanto (Jurnal Matematika Sains dan Teknologi, 2008)
White lily, Crinum asiaticum L (Amaryllidaceae) produce secondary metabolite called galantamine which has been developed to cure alzheimer desease. The purpose of this research was to explore the habitat of C. asiaticum which produces a high yield of galantamine. The bulb of C. asiaticum from four different locations which has altitudes ranging from 0-1250 meters above sea level was taken. Those locations were Santolo Beach-Garut, Cijambe-Subang, Dago-Bandung and Cikole-Lembang. The bulb was extracted and galantamine concentration was determined using HPLC (High Performance Liquid Chromatography). Parameters such as pH, humidity, soil organic content were also measured. The results showed that the bulb taken from Cikole had the highest galantaminecontent (63.592 mg/g). The results also showed positive correlation between altitude and galantamine content (r=0.843). However, galantamine content had no correlation with the size and weight of C. asiaticum bulb (r=0.0583). In relation to environmental condition, there was positive correlation between soil organic with galantamine content (r=0.862). Further, nitrogen concentration tends to affect the production of galantamine (r=0.848).